Pengembangan Usaha Produksi Mie Kering dan Basah di UMKM Lampionmas Banjaran, Kecamatan Taman, Kabupaten Pemalang - Tri Handayani; Hendra Hendra; Lavin Roro Shasita; Laili Ismatun Ningsih; Citra Karisma Deviani; Dian Arbaina; Olivia Natasya (Jurnal Kabar Masyarakat, 2025)
The UMKM that is the object of Team 3's community service activities is the UMKM "Mie Lampionmas" located on Jalan Bali No. 92 RT 03/RW 06 Banjaran Taman-Pemalang, Central Java. This UMKM produces semi-finished food ingredients, namely wet noodles and dry noodles. The purpose of implementing this community service activity is to provide assistance in business development in UMKM by identifying problems that exist in UMKM, and trying to provide alternative solutions. After conducting the observation stage, several problems were found faced by UMKM, including not having a production process video, the appearance of social media and e-commerce is not attractive, the business location is not listed on Google Maps, the P-IRT has expired, the logo is not attractive, does not have an organizational structure and business profile, the business banner is not suitable for use, does not have a price list (catalog), promotional materials, pamphlets and promotional videos, has not determined the HPP clearly and simple financial reports. After carrying out the observation stage, several business development assistance programs were formulated, including making videos of the production and promotion process, optimizing social media and e-commerce, creating Google Maps locations, extending P-IRT and updating passwords, updating logos, creating organizational structures, profiles and creating new banners, creating price lists (catalogs), pamphlet promotions, calculating COGS, recording simple financial reports. After analyzing and applying the KKU program to the MSMEs, it resulted in positive impacts, including the MSMEs having videos for promotional materials, attractive social media and e-commerce displays, having location points on Google Maps, valid P-IRT and being able to log into the OSS account again, having a logo, organizational structure, business profile, banner, price list, promotional pamphlet, and calculating COGS and clear financial reports.